十二年國教學校本位課程發展與實踐之個案分析：以一所國小參與前導學校協作計畫為例 A Case Analysis for the Development and Praxis of School-Based Curriculum of 12-Year Basic Education - 潘志煌 Chih-Huang Pan; 何育真 Yu-Chen Ho (Higher Education Foundation, 2019)
2019年8月起，教育部正式推動《十二年國民基本教育課程綱要》，並逐年實施課程綱要規劃的學校本位課程。《十二年國民基本教育課程綱要》以素養導向取代九年一貫課程綱要的能力本位，期許不僅是擁有帶著走的能力，更要藉由培養核心素養來強化學生，將能力應用於生活情境中，促進解決問題的實踐行動力，以彰顯學生作為學習主體的意義和價值。本研究主要是以一所參與教育部2016～2018年核定補助推動前導協作計畫的國小為例。探究其依據《十二年國民基本教育課程綱要總綱》，發展學校本位課程雙主軸「閱讀增能、運動樂活」，結合及納入校內行動學習、國際教育和藝文深耕推動計畫的課堂教學，並分析學校在發展課程及教學實踐歷程中，面臨的問題及其因應策略，以提供教師反思素養導向教學的專業能力和發展學生自主學習的可能性。 Beginning in August 2019, the Ministry of Education officially implemented the 12-Year Basic Education Curriculum Outline and put into practice the school-based curriculum year by year. The 12-Year Basic Education Curriculum Outline replaced the 9-year ability-based curriculum with competency-based instruction. Not only did the 12-year basic education curriculum put emphasis on the abilities that learners could use in daily life, but it also empowered learners by cultivating the core competencies. By way of the implementation of the curriculum, the learners could apply many abilities to real life and promote the power for action of solving problems to manifest the value of their subjectivity. The study aimed to explore the content of a pilot project that an elementary school granted by the Ministry of Education from 2016 to 2018. It explored the development of the school-based curriculum framed in the 12-Year Basic Education Curriculum Outline. Under the course of "reading empowerment and sporting lohas," the pilot project combined the action learning with international education and advanced arts project included in the classroom teaching. In addition, the study analyzed the diffi culties encountered in the process of teaching practices and coping strategies. According to the analysis, it provided teachers to refl ect on the professional abilities of competency-based instruction and develop the possibility of learners' autonomous learning.